Analysis of key success factors in implementing the balanced scorecard to improve hospital performance - Yull, Anatasia Agatha; Mulyani, Rizka Rosa Dwi (Publisia: Jurnal Ilmu Administrasi Publik, 2024)
Implementing the Balanced Scorecard (BSC) in hospitals has become an essential focus in improving organisational performance in the healthcare sector, especially in Indonesia, which faces unique challenges in terms of resources and infrastructure. This article aims to identify and analyse the critical success factors in implementing BSC in hospitals, with the hope of providing practical recommendations for management. The method used in this research is a systematic literature review, which involves a comprehensive analysis of various previous studies on implementing the Balanced Scorecard (BSC) in the healthcare sector. The research findings indicate that factors such as resource utilisation efficiency, patient satisfaction, management commitment, employee participation, and strategic alignment are crucial elements that significantly influence the success of BSC implementation. Implementing the Balanced Scorecard (BSC) in hospitals is an effective way to improve performance. Key success factors include efficient use of resources, patient satisfaction, and strong management support.